2010
DOI: 10.1007/s10458-010-9158-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling agents based on aspiration adaptation theory

Abstract: Creating agents that realistically simulate and interact with people is an important problem. In this paper we present strong empirical evidence that such agents should be based on bounded rationality, and specifically on key elements from Aspiration Adaptation Theory (AAT). First, we analyzed the strategies people described they would use to solve two relatively basic optimization problems involving one and two parameters. Second, we studied the agents a different group of people wrote to solve these same pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Furthermore, their solution has many non-intuitive properties. Nevertheless, as evidenced in the results section (and in prior literature [14,69]), both people and the agents they program fail to follow the optimal strategy when engaged in sequential economic search. Supplying the theoretic-optimal solution for the economic search to the searcher is not always feasible.…”
Section: Modeling Choice As Structured Explorationmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, their solution has many non-intuitive properties. Nevertheless, as evidenced in the results section (and in prior literature [14,69]), both people and the agents they program fail to follow the optimal strategy when engaged in sequential economic search. Supplying the theoretic-optimal solution for the economic search to the searcher is not always feasible.…”
Section: Modeling Choice As Structured Explorationmentioning
confidence: 59%
“…First, it can validate or invalidate the effectiveness of different heuristics, which have been proven to be useful in extensive experimentation with agents, when applied to people. The level of similarity between peoples' strategies and agents' strategies is not conclusive; some work suggests a relatively strong correlation between the behaviors of the two [14], while in other work the agents have been reported to act different than people to some extent [26,69]. Second, it is notable that while agents can be programmed only by people with programming skills, the experiments with people as decision makers enable testing the approach with the general population.…”
Section: Agent-based and Human-based Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in more complex environments a lack of data makes it unfeasible to elicit an accurate model with machine learning alone. In these types of problems we found that using attributes from cognitive models allowed for significantly more accurate models than models created from machine learning or the cognitive models alone (Rosenfeld and Kraus 2009;Rosenfeld and Kraus 2012;Zuckerman, Kraus, and Rosenschein 2011).…”
Section: General Methodology and Related Workmentioning
confidence: 99%